Analisis Gerak Harmonik Sederhana Sebagai Model Getaran Dalam Sistem Rekayasa Modern - Meydiyah Salsa Bila; Nurhamidah Nurhamidah; Faizatul Mabruroh; Yuli Agustina Rahayu; Muhamad Akbar Mahadva Yuda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the characteristics of simple harmonic motion (SHM) through pendulum experiments and the application of video analysis technology using the Tracker application as a model to understand vibration behavior in modern engineering systems. The experiment was conducted by varying the length of the pendulum string and measuring the period, frequency, and gravitational acceleration of the observations. Data were obtained through two methods, namely direct measurement using a stopwatch and digital analysis using the Tracker application to track the position, speed, and acceleration of the pendulum motion more accurately. The results show that the pendulum period increases with the length of the string, in accordance with the theoretical equation T = 2π√(l / g). Analysis using Tracker provides gravitational acceleration values ​​ranging from 8.15 m / s² to 8.99 m / s², which is close to the value of Earth's gravity (9.8 m / s²). The position-time and velocity-time graphs show a sinusoidal pattern consistent with the characteristics of SHM. The linear relationship between the square of the period T^2 and the length of the string l strengthens the agreement between the experimental results and the theory of SHM. Furthermore, the study also demonstrates the relevance of GHS in modern engineering systems such as vehicle suspension, vibration sensors, and the swing system on the Kora-Kora ride, which follow a similar oscillation pattern. The implementation of the Tracker application has been shown to improve the accuracy of the analysis by displaying motion data quantitatively, thus strengthening the understanding of GHS as a fundamental vibration model in engineering technology. Overall, this study confirms that simple harmonic motion is not only a theoretical concept but also an important foundation for understanding vibration dynamics in various modern mechanical systems.